Penerapan Model Pembelajaran Kooperatif Tipe Pair Checks Untuk Meningkatkan Kemampuan Pemahaman Konsep Operasi Hitung Berbagai Bentuk Pecahan Pada Siswa Sekolah Dasar - Retno Suprihatin; H Soegiyanto; Lies Lestari (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
The objective of this research is to improve the ability of understanding of the concept arithmetic operation on various forms of fractions of the students in Grade VI of State Primary School Karangasem IV No. 204 of Surakarta in Academic Year 2017/2018. It used the classroom action research with two cycles. The activities in each cycle were planning, implementation, observation, and reflection. The subjects of the research were the classroom teacher and the students as many as 33. Its data were collected through observation, indepth interview, test, and documentation. They were validated by using data source and data collection technique triangulations and analyzed by using the interactive model of analysis comprising four stages namely: data collection, data reduction, data display, and conclusion drawing. The results showed the average class score was of 61.42 with the classical learning completeness of 39.39%. Following the treatments, it became 79.17 with the classical learning completeness of 75.76% in Cycle I and 86.42 with the classical learning completeness of 90.91% in Cycle II. Based on the result of the research, it can be concluded that the application of the cooperative learning model of pair checks type could improve the ability of understanding of the concept arithmetic operation on various forms of fractions of the students in Grade VI of State Primary School Karangasem IV No. 204 of Surakarta academic year 2017/2018.